1996
DOI: 10.1016/0167-4889(96)00036-5
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning and characterization of rat Clk3, a LAMMER kinase predominately expressed in testis

Abstract: A cDNA clone of a protein kinase with high similarity to the Clk (Cdc2-like kinases) subfamily was isolated from a rat brain library and characterized. Its deduced amino acid sequence exhibited a 99% identity with human Clk3 and was therefore designated rat Clk3. In addition to the protein kinase domain, the sequence (490 amino acids) comprises an N-terminal domain with a strikingly high portion of basic amino acids. A glutathione S-transferase fusion protein of Clk3 catalyzed autophosphorylation of the kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…With all kinases of the DYRK family, incorporation of 32 P into H3 was greatly reduced or completely abolished in the mutant protein, clearly indicating that Thr-45 is the main phosphorylation site in histone H3 for DYRK-related kinases. For comparison, GST-CLK3 was included as a more distantly related protein kinase (18). Large amounts of the kinase were required to achieve detectable phosphorylation of rH3, and no difference was observed between rH3 and rH3-T45A (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With all kinases of the DYRK family, incorporation of 32 P into H3 was greatly reduced or completely abolished in the mutant protein, clearly indicating that Thr-45 is the main phosphorylation site in histone H3 for DYRK-related kinases. For comparison, GST-CLK3 was included as a more distantly related protein kinase (18). Large amounts of the kinase were required to achieve detectable phosphorylation of rH3, and no difference was observed between rH3 and rH3-T45A (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Protein Kinases and Substrates-The expression plasmids for GST-DYRK1A, GST-DYRK2, GST-DYRK3, and GST-CLK3 have been described earlier (1,2,18). An NcoI site at base pair 1624 of the rat cDNA was used to create a C-terminal deletion (amino acids 500 -763, numbering refers to Swiss-Prot accession number Q63470) in GST-DYRK1A-⌬C.…”
Section: Methodsmentioning
confidence: 99%
“…mRNA expression revealed by Northern blot analysis showed that PRPK may be functioning considerably in the testes in vivo. Testis-specific protein kinases have been reported (22)(23)(24). Both tssk1 and tssk2 appear in the adult testis and may play a role in the last stage of spermatid maturation (24).…”
Section: Discussionmentioning
confidence: 99%
“…In normal tissues, only the testis expresses TOPK mRNA. Testis-specific protein kinases have been reported (27)(28)(29)(30), and some spermatogenetic roles of these kinases have been debated; however, the precise mechanisms of these kinases, such as target specificity and signaling cascades, remain to be elucidated. On the other hand, TOPK phosphorylates p38 MAPK, and its signaling can be examined from the viewpoint of a MAPK cascade in the testis.…”
Section: Fig 12mentioning
confidence: 99%